ANALISIS DAN SIMULASI MODUL HUMAN RESOURCE MENGGUNAKAN WEBSITE ODOO PADA PT. XYZ - Aisah, Aisah; Budiyanto, Asri (Jurnal Dinamika UMT, 2022)
PT. XYZ is a company that focuses on managing outsourcing services based on labor providers (procurement workforce) and employment charters (service management). Sumer human power or labor is an asset and determining factors in the success of a company if not managed with the best assets can be a factor that interferes with the process of isnis and performance of the company's objectives. Based on the observation, it is known that the data collection process of PT XYZ Group employees always use Microsoft Excel and the management is optimal because it is done manually.In addition, data search is always done through a relatively time-consuming and erisiko stack of documents in terms of data security and inefficient in terms of storage. This research is supported by existing issues to support the HR department of PT. XYZGroup in developing integrated information systems erupa Enterprise Resource Planning (ERP) to manage recruitment modules. By storing all recruitment activities in the Odoo app in real time the HR department can easily handle employee recruitment and manage and track stored data.